(untitled) (ESMAT Magazine, 2024)
The irremediable connection between Artificial Intelligence and the healthcare field raises crucial ethical questions that require an in-depth examination and a reinterpretation of the ethical values in force to date. On this basis, the philosophy of law is concerned with defending equity and justice as dogma of faith. These controversial situations are also reflected in the field of health, since they present different issues to be resolved on the application of Artificial Intelligence in the health field from the perspective of the Philosophy of Law, a topic that will focus the core of the research of this work. In this regard assert that Artificial Intelligence has had a significant impact on the field of health and health care in various areas of medicine, but at the same time raises important ethical issues that must be carefully considered for its proper application. In short, the introduction of Artificial Intelligence with a philosophical-legal reflection raises numerous challenges and sufficient reasons to trace a path of analysis on the nature of law, ethics, justice and the responsibility of professionals in the healthcare field. Legal philosophers are actively exploring these questions as Artificial Intelligence continues to transform the way the legal system interacts with technological advances from an ethical perspective.